2020
DOI: 10.1038/s41598-020-70712-9
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use and risk of hip fracture in patients with type 2 diabetes

Abstract: Type 2 diabetes mellitus (T2DM) is associated with a high rate of comorbidity, including osteoporosis and peptic ulcers. Proton pump inhibitors (PPIs) are a group of acid-suppressing drugs commonly used for treating peptic ulcers. However, observational studies have reported an association between PPI therapy and osteoporotic fractures. This study investigated the association between PPI use and hip fracture (HFx) among patients with T2DM. We conducted this population-based propensity-matched retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
1
11
0
3
Order By: Relevance
“…Several studies have demonstrated a significant positive association between osteoporosis and PUD [2,[12][13][14][15][16][17][18][19]. However, one study yielded a conflicting result regarding the association [26].…”
Section: Osteoporosis: a Complication Of Pudmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a significant positive association between osteoporosis and PUD [2,[12][13][14][15][16][17][18][19]. However, one study yielded a conflicting result regarding the association [26].…”
Section: Osteoporosis: a Complication Of Pudmentioning
confidence: 99%
“…Despite excellent efficacy and trivial short-term side effects, rising concerns regarding long-term adverse effects of PPI use such as the risk of osteoporosis-related fracture, vitamin B12 deficiency, renal injury, Clostridium difficile infection, community-acquired pneumonia, and dementia is emerging [11]. Several studies have demonstrated a significant positive association between PUD, long-term PPI use, and increased incidence of osteoporotic fracture risk [2,[12][13][14][15][16][17][18][19]. Therefore, this systematic review aims to explore the association between osteoporosis and PUD and understand the different mechanisms by which osteoporosis emerges as a complication of PUD.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors showed the presence of a positive association between the use of proton pump inhibitors (PPIs) and hip fractures in postmenopausal women [92], men [93], elderly subjects [94,95], and also in patients with type 2 diabetes [96]. Recently, it has been observed that PPI use was associated with bone fractures in a dose-dependent fashion and also in patients with liver cirrhosis [97].…”
Section: Calcium Reduced Bone Mineral Density Fractures and Impaired Gastric Acid Secretionmentioning
confidence: 99%
“…Diabetes mellitus type 2 (T2DM) is a widespread metabolic condition globally. [2]. It affects bone homeostasis leading up to 3-fold elevated hip fracture hazard comparing to those healthy individuals.…”
Section: Introductionmentioning
confidence: 99%